Additive manufacturing of periodic ceramic substrates for automotive catalyst supports. Issue 6 (7th July 2017) - Santoliquido, Oscar; Bianchi, Giovanni; Dimopoulos Eggenschwiler, Panayotis; Ortona, Alberto
Abstract: Additive manufacturing (AM) has the potential to revolutionize engineering because of its advantages in the product development phase. The revolution consists in the new approach of components' design by function and no longer by manufacturability. This is the motivation driving authors to design and realize by additive manufacturing a new catalyst support for automotive exhausts which is no longer constrained by the industrial manufacturing methods and thus allows an optimized flow of the exhaust gasses. This work presents a new class of periodic cellular ceramic substrates. To authors' knowledge this is the first time such kind of structures are employed in the automotive field. After a review the different ceramic AM techniques which are currently utilized in the production of highly complex ceramic architectures, the most suited one was selected and several samples were produced by AM. They were finally characterized via microscopic analysis (SEM, CT) compression tests revealing the best printing configuration for their mechanical behavior.